1997
DOI: 10.1111/j.1365-2621.1997.tb15014.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin E Affects Lipid Oxidation and Total Volatiles of Irradiated Raw Turkey Meat

Abstract: Breast and leg meat patties, prepared from turkeys fed diets containing 25, 200, 400 or 600 IU of dl-␣-tocopheryl acetate (TA) per kg diet, were irradiated at 0 or 2.5 kGy with vacuum or loose packaging. The effects of dietary TA on storage stability and production of volatiles in irradiated raw turkey meat were determined. Dietary TA at Ͼ 200 IU/kg decreased lipid oxidation and reduced total volatiles of raw turkey patties after 7-days of storage. However, the antioxidant effects of dietary TA were more notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…However, the rate of formation of hexanal as a result of irradiation dose level was much higher in FRG groups than in CON groups contrasting the trends described previously for TBA-RS. The mechanisms of volatile production in irradiated meats are not fully understood, but many published works suggest that the radiolytic products of proteins as well as lipid oxidation by-products are responsible for the offodour in irradiated meats (Ahn et al, 1997(Ahn et al, , 1998Ahn, Jo, Du, Olson, & Nam, 2000;Ang & Lyon, 1990;Hampson et al, 1996;Hashim, Resurrecció n, & MacWatters, 1995;Lefebvre, Thibault, Charbonneau, & Piette, 1994;Patterson & Stevenson, 1995). We presume that the possible higher intramuscular fat content of FRG samples (Cava et al, 2000) which should have been the contributing factor for its high hexanal formation after irradiation.…”
Section: Hexanal Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the rate of formation of hexanal as a result of irradiation dose level was much higher in FRG groups than in CON groups contrasting the trends described previously for TBA-RS. The mechanisms of volatile production in irradiated meats are not fully understood, but many published works suggest that the radiolytic products of proteins as well as lipid oxidation by-products are responsible for the offodour in irradiated meats (Ahn et al, 1997(Ahn et al, , 1998Ahn, Jo, Du, Olson, & Nam, 2000;Ang & Lyon, 1990;Hampson et al, 1996;Hashim, Resurrecció n, & MacWatters, 1995;Lefebvre, Thibault, Charbonneau, & Piette, 1994;Patterson & Stevenson, 1995). We presume that the possible higher intramuscular fat content of FRG samples (Cava et al, 2000) which should have been the contributing factor for its high hexanal formation after irradiation.…”
Section: Hexanal Contentmentioning
confidence: 99%
“…Therefore, the susceptibility of irradiated muscle tissues to lipid oxidation and the intensity of the changes are closely related to the nature, proportion, degree of unsaturation of fatty acids and the composition of phospholipids in cell membrane besides antioxidant concentrations in muscle and the irradiation dose and the packaging method (Ahn et al, 1997;Ahn, Olson, Jo, Love, & Jin, 1999;Gray, Gomaa, & Buckley, 1996;Morrissey, Brandon, Buckley, Sheehy, & Frigg, 1997;Nanke, Sebranek, & Olson, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation has been reported to increase 2-thiobarbituric acid-reactive substances (TBA-RS) in different meat species, packaging and storage conditions (Hampson, Fox, Lakritz, & Thayer, 1996;Ahn et al, 1997;Du, Ahn, Nam, & Sell, 2000). In addition, previous studies have shown that irradiation can induce oxidative deterioration of fatty acids and consequently generate offflavours that comprise consumer's acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…FD patties illustrate some increase due to some lipid oxidation during freeze drying, which supports NASA recommendation for using nitrogen flush chambers. Ahn et al (1997Ahn et al ( , 1998 reported that preventing oxygen exposure after cooking was more important for cooked meat quality than irradiation or storage time of raw meat, and lipid oxidation was a significant problem in irradiated meat only when it was stored aerobically (Merritt et al1975;Ahn et al 1997). Table 3 shows the volatile compounds of non-irradiated or freeze dried cooked beef patties with different treatments at day 0.…”
Section: Resultsmentioning
confidence: 99%